The Influence of Personality Types and Motivation on Employee Performance at Tempeh Lumajang Public High School - Via Lailatur Rizki (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study analyzes the effect of personality type and motivation on the performance of the employees of Tempeh Lumajang Public High School. This study uses a quantitative approach that is hypothesis testing. The population used was all employees of the State Senior High School of Tempeh, and the sampling used the census method. The data analysis method used in this article is multiple regression analysis. The results showed that the personality type had a significant positive effect on the performance of the employees of the Tempeh Lumajang Public High School. Motivation has a significant positive effect on the performance of the employees of the Tempeh Lumajang Public High School.